2022
DOI: 10.25259/sni_73_2022
|View full text |Cite
|
Sign up to set email alerts
|

Middle meningeal artery embolization before craniotomy for infected organizing chronic subdural hematoma: A case report and review of the literature

Abstract: Background: Organizing chronic subdural hematoma (OSDH) is intractable and its radical treatment remains controversial. Middle meningeal artery embolization has emerged as an adjunctive treatment to craniotomy for OSDH. Case Description: The patient is an 86-year-old man. He had been taking warfarin for atrial fibrillation and was referred to the department for the treatment of bilateral chronic subdural hematoma (CSDH), which was found on head computed tomography after a fall. Bilateral burr hole drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 10 , 14 ) This method has since been reported effective in cases with concomitant antithrombotic medications, 15 , 16 ) CSDH in elderly patients, 17 , 18 ) CSDH in cases of dural metastases from cancers of other organs, 19 , 20 ) and infectious CSDH. 21 ) Additionally, MMA embolization is considered a preferred therapeutic option for CSDHs with spontaneous intracranial hypotension to buy time before the epidural blood patch starts working. 22 , 23 ) Many reports show that MMA embolization is effective in children with congenital heart disease who are taking antithrombotic drugs and children with CSDH associated with head trauma.…”
Section: Variations Of Csdh Indicated For Mma Embolizationmentioning
confidence: 99%
“… 10 , 14 ) This method has since been reported effective in cases with concomitant antithrombotic medications, 15 , 16 ) CSDH in elderly patients, 17 , 18 ) CSDH in cases of dural metastases from cancers of other organs, 19 , 20 ) and infectious CSDH. 21 ) Additionally, MMA embolization is considered a preferred therapeutic option for CSDHs with spontaneous intracranial hypotension to buy time before the epidural blood patch starts working. 22 , 23 ) Many reports show that MMA embolization is effective in children with congenital heart disease who are taking antithrombotic drugs and children with CSDH associated with head trauma.…”
Section: Variations Of Csdh Indicated For Mma Embolizationmentioning
confidence: 99%
“…3,5 Owing to a high rate of recurrence and perioperative complications associated with open surgery, MMA embolization is emerging to be not only an adjunct but also a stand-alone treatment option for chronic subdural hematoma. 6,7 In a prospective study, Ban et al 7 reported MMA embolization to be a superior option than conventional treatment options. In this same study, treatment failure for MMA embolization was reported to be only 1.4% as compared with 27.5% among patients who underwent surgical drainage.…”
mentioning
confidence: 99%